Justification of punishment - Zaibert, Leo (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
The traditional approach to the problem of the justification of punishment suffers from an exaggerated axiological narrowness. The central concern has always surrounded the question as to whether or not a certain punishment is permissible. There is no doubt that this is an important problem, although it is not the only problem. Punishments that we may be permitted in inflicting can also be indecent or repugnant – and the analysis of these important characteristics is impossible from the perspective afforded by the overly narrow traditional approach.